2013
DOI: 10.1097/hjh.0b013e32836184b5
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure levels and brain volume reduction

Abstract: These findings provide evidence that high BP levels lead to brain volume reduction, specifically in hippocampus, and may be an important factor that contributes to neurodegeneration in Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 55 publications
7
133
1
2
Order By: Relevance
“…Diabetes and hypertension were added as covariate due to their associations with neurodegenerative processes, particularly in the hippocampus. 33,34 Hippocampal atrophy was assessed by using wave 2 volume as dependent variable and controlling for wave 1 volume as covariate in the analyses, while also controlling for elapsed time between assessments. In addition, because the image acquisitions were different between waves, the difference in ICV between wave 1 and wave 2 was also controlled for by entering it as a covariate in the analyses, an approach already applied elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and hypertension were added as covariate due to their associations with neurodegenerative processes, particularly in the hippocampus. 33,34 Hippocampal atrophy was assessed by using wave 2 volume as dependent variable and controlling for wave 1 volume as covariate in the analyses, while also controlling for elapsed time between assessments. In addition, because the image acquisitions were different between waves, the difference in ICV between wave 1 and wave 2 was also controlled for by entering it as a covariate in the analyses, an approach already applied elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7] It has been shown that vascular risk factors such as hypertension, diabetes mellitus, and smoking are associated with accelerated brain atrophy. 6,[8][9][10] In parallel, several studies have shown that a smaller brain volume is often accompanied by a lower cerebral blood flow (CBF). 11,12 One proposed mechanism is that a smaller brain volume leads to reduced metabolic demand, which in turn may lead to a lower CBF.…”
Section: Introductionmentioning
confidence: 99%
“…Hierdurch kann es zur Zellschädi-gung und Anreicherung von Beta-Amyloid kommen, das in der Alzheimer-Pathologie eine wesentliche Rolle spielt. In einem Review von 28 Studien wurde zusammenfassend dargestellt, dass in fast allen Studien eine signi kante Assoziation von hö-heren Blutdruckwerten mit einer Reduktion des Hirnvolumens -besonders des Hippocampus -bestand [23].…”
Section: Stellenwert Der Hypertonieunclassified